Comparison of efficacy of chlorhexidine alcohol scrub and povidone iodine scrub in hand cleansing in elective clean surgery - Takalkar, Yogesh P.; Garale, Mahadeo Namdeo; Somasundaram, Soundappan; Venkataramani, Karthik; Gothwal, Kalyansing N.; Pandrowala, Saneya A. (International Surgery Journal, 2016)
Background: Hand asepsis is the best prevention for surgical site infection (SSI). The surgeon uses different methods of surgical hand antisepsis. The present study was undertaken to compare and evaluate the efficacy of chlorhexidine alcohol versus povidone iodine in elective clean surgeries for prevention of SSI. Methods: We conducted a double blind, prospective, interventional study on patients undergoing elective clean surgeries in general surgical operation theatre of a tertiary care center. Surgeons were assigned randomly to use povidone-iodine 7.5% surgical scrub or chlorhexidine gluconate 2.5% prior to surgery. The number of patients who developed a surgical site infection was expressed as a percentage of the total. Incidence of surgical site infection was calculated individually in both the groups. Results: Both the groups were comparable in terms of various variables. Infection rates of both the groups were similar with respect to age, gender, duration of surgery, personal history of addictions. However, in case of comparison BMI in both groups in patients who had infection and it was observed that BMI was significantly different in both groups. In normal and overweight patients chlorhexidine group had more infection while moderately obese patient’s povidone-iodine group had more infection. Conclusions: Povidone-iodine 7.5% surgical scrub and chlorhexidine gluconate both are equally good scrubs in elective clean surgeries.